ANALISA PERUBAHAN KV TERHADAP KUALITAS CITRA DAN CTDI - I Gede Eka Sukanta; Made Sayang Pratista; I Wayan Angga Wirajaya; Anak Agung Aris Diarthama (JRI (Jurnal Radiografer Indonesia), 2022)
Background : Improved CT Scan image quality with tube variation once reported that higher tube voltage results in better image quality. But the study was conducted to evaluate the tube voltage of 80 kv to lower the dose so that the current of the tube is not increased. Some researchers recommend scanning with low tube voltage and properly adjusted tube current to reduce radiation doses on brain CT scans. However, so far there has never been an evaluation of kV values on image quality and CTDI in the head MSCT and at Sanjawani Hospital to analyze Kv changes to image quality and CTDI multislice computed tomography on phantoms. Methods:The study was conducted on the Phantom using the parameters of the HEAD CT scan examination. This research method is quantitative research with an experimental approach. The study was conducted on the Phantom using the parameters of the HEAD CT scan examination. Results: This study was conducted by collecting kV variation data of 70, 80, 100, 120, and 140 scanned 3 times. Conclusion : The results obtained the output of spss friedman test spatial resolution, contrast resolution, nooise and artifact, the highest rank is at kV tube voltage 120. Ctdi value obtained with kV variari, is in accordance with bapeten / IDRL 2021 recommendations.